Answer:
(a) [tex](-i)^{i}=e^{i \log (-i)}=e^{i (\log \lvert -i \rvert +i(\arg (-i)+2\pi n))}=e^{i(0+i(-\frac{\pi }{2}+2\pi n))}=e^{-(-\frac{\pi}{2}+2\pi n)}=e^{\frac{\pi}{2}-2\pi n[/tex], where [tex]n\in \mathbb{Z}[/tex]
(b)[tex](-1)^{i}=e^{i \log (-1)}=e^{i (\log 1 +i(\pi+2\pi n))}=e^{-(\pi+2\pi n)}[/tex], where [tex]n\in \mathbb{Z}[/tex].
Step-by-step explanation:
Let's remember the definition of complex exponents. If [tex]z[/tex] is a nonzero complex number and [tex]c[/tex] is a complex number, we define [tex]z^{c}[/tex] by
[tex]z^{c}=e^{c \log z}[/tex]
Where the [tex]\log[/tex] function is the complex logarithm function. That is to say, [tex]\log z=\log \lvert z\rvert + i(\arg z+2\pi n)[/tex], where [tex]n\in \mathbb{Z}[/tex]. With this in mind we can calculate the given powers as follows:
(a) [tex](-i)^{i}=e^{i \log (-i)}=e^{i (\log \lvert -i \rvert +i(\arg (-i)+2\pi n))}=e^{i(0+i(-\frac{\pi }{2}+2\pi n))}=e^{-(-\frac{\pi}{2}+2\pi n)}=e^{\frac{\pi}{2}-2\pi n[/tex], where [tex]n\in \mathbb{Z}[/tex]
(b)[tex](-1)^{i}=e^{i \log (-1)}=e^{i (\log 1 +i(\pi+2\pi n))}=e^{i(0+i(\pi +2\pi n))}=e^{-(\pi+2\pi n)}[/tex], where [tex]n\in \mathbb{Z}[/tex].
This are all the values of the given powers.